2014
DOI: 10.3390/galaxies2020199
|View full text |Cite
|
Sign up to set email alerts
|

Mass Distribution in Rotating Thin-Disk Galaxies According to Newtonian Dynamics

Abstract: An accurate computational method is presented for determining the mass distribution in a mature spiral galaxy from a given rotation curve by applying Newtonian dynamics for an axisymmetrically rotating thin disk of finite size with or without a central spherical bulge. The governing integral equation for mass distribution is transformed via a boundary-element method into a linear algebra matrix equation that can be solved numerically for rotation curves with a wide range of shapes. To illustrate the effectiven… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(48 citation statements)
references
References 23 publications
(75 reference statements)
2
44
0
Order By: Relevance
“…The absence of energy along the special axis is not accounted for in orbital models, which leads to excess mass and the inference of non-baryonic matter. Such matter has not been detected despite expenditures of billions of dollars over several decades, motivating alternative models [15,[23][24][25][27][28][29]. Spin models give a reasonable mass for 14 large galaxies; see the table in [10].…”
Section: Shape and Spinmentioning
confidence: 99%
See 2 more Smart Citations
“…The absence of energy along the special axis is not accounted for in orbital models, which leads to excess mass and the inference of non-baryonic matter. Such matter has not been detected despite expenditures of billions of dollars over several decades, motivating alternative models [15,[23][24][25][27][28][29]. Spin models give a reasonable mass for 14 large galaxies; see the table in [10].…”
Section: Shape and Spinmentioning
confidence: 99%
“…If the problem to be addressed involves multiple masses, then the effect of their combined forces on some external test mass involves integrating over several surfaces and summing, as illustrated in Figure 2e. For RC, the problem is that both the mass inside (M in ) and mass outside some equatorial radius can affect the particle orbiting at that radius (Figure 2b), as shown by force models [27]. Unless the mass outside the radius of interest is distributed spherically, or spheroidally if rotating, it contributes a force in addition to that represented by (10) and must be considered with another surface and volume.…”
Section: Limitations In Applying Poisson's Equationmentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequent application of Milgrom's modified Newtonian dynamics (MOND) formulation demonstrated that dark matter is not needed for diverse galaxy types [11,12]. Concurrently, NOMs became more sophisticated, but with two rare exceptions [2,13], provide large amounts of dark matter, ϳ75% for the Milky Way and many others [4,14,15] and up to 99.9% for dwarf galaxies [16]. Because these ambiguous forward models provide dark matter exceeding cosmological estimates of ϳ27% [17], this component is arbitrarily minimized during fitting [3,5,6,18].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, that centers of spiral galaxies spin like tops is unexplained [3], although this trend can be reproduced with fitting parameters. Lastly, recent force-fitting models [2,13] that depart from mainstream NOMs by accounting for effects of mass outside the orbit of interest, do not require dark matter.…”
Section: Introductionmentioning
confidence: 99%